Auxiliary verb constructions in the languages of Africa - Gregory D. Anderson (LibraryPress@UF, 2011)
Auxiliary verb constructions–constructions with two or more elements of verbal origin, one of which expresses functional semantic categories–are widespread among the languages of Africa. In the following discussion, I present a typology of inflection in auxiliary verb constructions [AVCs] in the languages of Africa. While there are several macro-patterns of distribution seen in the various African languages, only a small selection are presented in some detail here, viz. the doubled and split/doubled inflectional patterns, along with the fusing of subject markers and TAM/polarity auxiliaries into so-called tensed pronouns that are relatively more common in AVCs across the languages of the continent than in most other parts of the world.